Ingerência ecopolítica: a soberania brasileira à luz do direito humano e fundamental ao meio ambiente ecologicamente equilibrado - Fraga, Raíssa Macedo Peçanha da (2021)
This study aims to analyze the possibility of ecological interference in the Brazilian territory in the light of the growing deforestation and fires in its main biomes, as well as in front of the clear inability of Brazil to promote an effective protection of nature and to repair the environmental crisis. For this purpose, the fundamental concepts of the institute of sovereignty will be pointed out, presenting the historical evolution of the term, from its birth in the doctrine of Jean Bodin, to the current postmodern conception achieved with the consolidation of international law and the interdependence between the nation-states. Subsequently, the main legal and normative mechanisms aimed at protecting the environment will be indicated, at the international and national ambits, presenting the country's jurisprudential view attributed to the environment and concrete data on human action in the face of Brazilian biomes. Finally, the possibility of relativizing state sovereignty in favor of the fundamental and human right to an ecologically balanced environment will be analyzed. From a methodological point of view, bibliographic research was used as a methodology, under a dialogic approach, exercising a dialogue between the notion of state sovereignty and the fundamental right and duty to protect the environment, in order to conclude, without exhausting the studies on the theme, due to the possibility of external interference in Brazil, in favor of the environment, in view of a relevant ecological risk that justifies cooperation between the nations